Ekuitas Merk Dan Keterlibatan Pelanggan Terhadap Minat Beli Di E-Commerce Tiktok Shop : Studi Kasus Pada Konsumen Celana Jeans Wanita Ditoko Jiniso - Desvianey Igamawarti; Febsri Susanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to increase brand equity and customer involvement in purchasing interest in the e-commerce TikTok shop among consumers of women's jeans at the Jiniso shop. This type of research is quantitative and the population in this study was 255,800 people. The sampling technique used is non-probability sampling, namely using accidental sampling, a sampling procedure that selects samples of people who are most easily accessible. The number of samples selected was 100 people from the results of calculations using the Slovin formula. The data sources for this research are primary and secondary data sources, while the data collection techniques are through observation and questionnaires. Using research instrument data analysis techniques (validity test, reliability test, and descriptive analysis), classic assumption tests (normality test, multicollinearity test, and heteroscedasticity test), and multiple linear regression analysis followed by hypothesis testing with the help of the SPSS application. The research results show that brand equity and customer involvement have a positive and significant effect on purchasing interest in the e-commerce TikTok shop among consumers of women's jeans at the Jiniso shop.